Pengaruh Modifikasi Pipa Pendingin Terhadap Efektivitas Induced Draft Cooling Tower LBC-50 - Muhammad Fairuz Naufal; amri abdulah; Yadi Heryadi; Apang Djafar Shieddieque; Dede Ardi Rajab; Sri Suhartini (Sekolah Tinggi Teknologi Wastukancana, 2025)
This study aims to analyze the performance enhancement of an induced draft cooling tower through modifications to the water distribution piping line, as well as to evaluate the thermal and hydraulic performance before and after modification. The initial system exhibited relatively low cooling effectiveness due to uneven water distribution and limited heat transfer between air and water within the tower. Therefore, the piping layout was redesigned to improve flow uniformity, enlarge the air–water contact area, and minimize heat losses, thereby enhancing overall cooling efficiency. The experimental tests were conducted under identical operating conditions with an inlet water temperature of 38 °C. The results showed that the outlet water temperature decreased from 33.78 °C (before modification) to 28.95 °C (after modification). The range increased from 5.17 °C to 9.12 °C, while the approach decreased from 4.68 °C to 2.61 °C, indicating a more effective cooling process approaching ideal conditions. Furthermore, the cooling capacity showed a substantial increase from 21,717.4 kW to 61,515.1 kW, signifying that the modified cooling tower can dissipate a greater amount of heat and support higher cooling demands in industrial operations. In addition, the system effectiveness improved from 52.45% to 77.58%, demonstrating a significant enhancement in heat transfer efficiency as a result of improved fluid distribution. On the other hand, the total head loss increased from 39.11 m to 63.71 m, indicating higher flow resistance due to the new configuration, but it remained within acceptable limits. Overall, the study concludes that modifying the piping line in the induced draft cooling tower significantly improves thermal performance, cooling effectiveness, and capacity, making the redesigned configuration a viable approach to increase the efficiency of large-scale industrial cooling systems..